Social work practice in the criminal justice system - Patterson, George T. (London : Routledge, 2012)
'The criminal justice system, with its complex policies and procedures and its focus on deterrence, punishment, and rehabilitation, can be a difficult system to understand. Forensic Social Work presents an overview of the the criminal justice system, exploring the network of systems which comprise it. Integrating social work values and a commitment to social justice, this textbook explores how social workers can practice to address social problems within the criminal justice system and promotes the development of knowledge, skills and critical reflection in this increasingly important area of practice. In addition to covering the four key areas for social work practice law enforcement; courts; corrections; and legislation it covers: Alternative programs and services, Special populations such as juveniles, women and sex offenders, Special topics such as reoffending, wrongful conviction and racial disparities. Social work skills in the criminal justice system. Looking at the challenges and opportunities of social work practice in the criminal justice system, this is the ideal text for students undertaking courses in forensic social work.'--
'The criminal justice system, with its complex policies and procedures and its focus on deterrence, punishment, and rehabilitation, can be a difficult system to understand. Social Work Practice in the Criminal Justice System presents an overview of the criminal justice system, exploring the network of systems which comprise it. Integrating social work values and a commitment to social justice, this textbook explores how social workers can practice to address social problems within the criminal justice system and promotes the development of knowledge, skills and critical reflection in this increasingly important area of practice. In addition to covering the four key areas for social work practice - law enforcement, courts, corrections, and legislation - it covers: Alternative programs and services Special populations - such as juveniles, women and sex offenders Special topics - such as reoffending, wrongful conviction and racial disparities The application of evidence-based practice principles in criminal justice. Looking at the challenges and opportunities of social work practice in the criminal justice system, this is the ideal text for social work instructors, students and practitioners working with or within the criminal justice system. Each chapter includes a summary of social work practice implications, key terms, and suggested further reading'--
Includes bibliographical references and index.
Keywords: Criminal justice, Administration of -- United States; Social work with criminals -- United States